The Mass Production of Religious Authority: A Study on a Ma'had Aly Program in South Sulawesi, Indonesia - Halim, Wahyuddin (Universitas Islam Internasional Indonesia, 2022)
The rise of new Muslim organizations in Indonesia after the reform movement in 1998 has produced a new type of religious authority, particularly through the emergence of popular preachers. Television and social media platforms are among the key factors in helping these new sources of religious authority gain instant popularity in the Muslim community. Many of those fitting this new type of preacher are relatively junior, starting their career by delivering religious speeches to diverse Islamic study groups in urban areas before appearing on television and various social media platforms. Their popularity has influenced the way the Muslim communities in Indonesia view and respect the status and role of traditional Islamic authority (ulama). For a long time, the traditional type of ulama has functioned as the most authoritative source of religious knowledge and learning for the Muslim community. This paper describes the important role of the graduates of a tertiary Islamic education program for producing junior ulama, the Ma’had ‘Aly As‘adiyah, in the field of Islamic education and da‘wa (Islamic preaching) and how it has adapted its teaching methodology to suit current developments in those fields. This research finds that while maintaining traditional da‘wa methods for local communities, some Ma‘had Aly graduates have also taken advantage of various new digital media platforms to reach more diverse and wider audiences. This research argues that Ma’had ‘Aly As‘adiyah has consistently trained and produced new ulama with high competence in various disciplines of Islamic knowledge and an ability to respond and adapt to contemporary socio-religious changes partly generated by the disruptive development of new media.